Development of Professional Teacher Competencies in the Contract of Subject Teacher Development in Manado City - Takalao, Christin Natalia; Egeten, Maxi M.; Waleleng, Grace J. (Journal La Edusci, 2024)
To be able to achieve quality education, professional teachers are needed. Subject Teacher Conference (MGMP) is one forum that can help improve teacher professionalism. This research aims to find out and analyze how Professional Teacher Competency Development is carried out in the Subject Teacher Deliberation Forum (MGMP) in Manado City. A qualitative approach was used in this research. Subject Teachers' Conference (MGMP) in Manado City as a forum for improving aspects of knowledge, pedagogy and professionalism of junior high school teachers in Manado City. By participating in MGMP activities and programs, teachers have better mastery of the material, mastering standards and competencies, learning theories and learning principles as well as the curriculum of the subjects taught. Activities in the Subject Teacher Deliberation Forum (MGMP) in Manado City must continue to be carried out routinely and sustainably. This research recommends that junior high school teachers must be committed to diligently participating in the activities or programs being implemented, because there are still teachers who do not regularly participate in activities because of their busy schedules. The management encourages its members to actively participate in MGMP activities and programs. Teachers who are not yet very adept at using technology in the learning process must continue to be accompanied and given training and allocated sufficient funds for sustainable implementation of the MGMP.